2002
DOI: 10.1095/biolreprod66.6.1656
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Receptor Chicken Ovalbumin Upstream Promoter Transcription Factors Inhibit Steroid Factor-1, Upstream Stimulatory Factor, and Activator Protein-1 Activation of Ovine Follicle-Stimulating Hormone Receptor Expression via Composite cis-Elements1

Abstract: The FSH receptor (FSHR) is selectively expressed in the granulosa and Sertoli cells in a development-dependent manner. Little is known regarding how the regulatory factors balance expression of this gene in ovarian cycles or spermatogenic stages. We have used the ovine FSHR promoter as a model system and identified a third regulatory element (RE-3) located at -197 to -171 of the strongest promoter. Gel mobility shift and antibody supershift assays demonstrated that nuclear factors c-Fos/c-Jun, steroidogenic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…In this regard, the transcriptional repressor, NR2F2, is of interest. It acts on multiple signaling pathways by inhibiting SF1, USF, and AP1 (Xing et al, 2002). NR2F2 is critical for limb bud outgrowth in mice (Lee et al, 2004), development of the inner ear, liver, and pancreas (Tang et al, 2005;Zhang et al, 2002), as well as venous identity (You et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the transcriptional repressor, NR2F2, is of interest. It acts on multiple signaling pathways by inhibiting SF1, USF, and AP1 (Xing et al, 2002). NR2F2 is critical for limb bud outgrowth in mice (Lee et al, 2004), development of the inner ear, liver, and pancreas (Tang et al, 2005;Zhang et al, 2002), as well as venous identity (You et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that integration of ECR regulatory activity with promoter transcription may require additional promoter sequences absent from the -220bp/+123bp construct used in these experiments, such as the SF-1 binding sites located between -743bp and -2700bp (Heckert, 2001). Previous studies postulated that SF-1 plays a combinatorial role in directing cell-specific Fshr expression by interacting with other transcription factors that have overlapping limited expression profiles (Heckert, 2001;Levallet et al, 2001;Xing et al, 2002). Thus, ECR regulation of Fshr transcription may only be revealed in the presence of SF-1 and its responsive region, and experiments are underway to explore the role of SF-1 in ECR transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Principle among these elements is the E-box, which is responsible for the majority of Fshr promoter activity and is required for binding and transcriptional induction of Fshr by the ubiquitous basic helix-loop-helix transcription factors Usf1 and Usf2 (Goetz et al, 1996;Heckert et al, 1998;Heckert et al, 2000). Additionally, the orphan nuclear receptor steroidogenic factor 1 (SF-1) activates the Fshr promoters from mouse, rat, and sheep (Heckert, 2001;Levallet et al, 2001;Xing et al, 2002). Since Sertoli and granulosa cells are a subset of SF-1 expressing cells, SF-1 may participate in activating cellspecific Fshr expression (Val et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiment found that sequence containing an E box was not only bound by USF protein but also was recognized by orphan receptor chicken ovalbumin upstream promoter transcription factors (COUP-TF orphan receptors). 17 In vivo genomic footprint analysis in the core promoter using nuclear proteins from Sertoli cells identified other important regulatory elements. They are an inverted GATA (TATC, -88/-85) and an E2F (TTTCGCG, -45/-39).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…17 Gel mobility shift and antibody supershift assay demonstrated nuclear factor c-Fos/c-Jun, steroidogenic factor-1 (SF-1), upstream stimulatory factor 1/2 (USF-1/2) and chicken ovalbumin upstream promoter transcription factor-1/2 (COUP-TF I/II) potentially bound to RE-3. Functional studies demonstrated USF-1/2, c-Fos/c-Jun and SF-1 were activators, whereas COUP-TFs were repressors.…”
Section: Transcription Factorsmentioning
confidence: 99%